A permissioned blockchain framework for security and privacy-preserving AMI in smart community - Soh, Kok Heong (Nanyang Technological University, 2021)
As every year past, technologies in the world are getting more and more advance. Storing and sending information using digital technology are also increasing as we speak. With Advanced Meter Infrastructure (AMI) being highly developed, the cybersecurity has become an import and valuable topic in the smart grid. Smart meter was invented to make data more efficiency and transparent for client to access. But it also increases the risk of data leak to unknown third party. Exploration of how a smart meter sends it data to the selected utility server. The experiment to enhance data security with use of encrypt code and blockchain system.